2008
DOI: 10.1152/ajpregu.00184.2008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the cough reflex by antitussive agents within the caudal aspect of the nucleus tractus solitarii in the rabbit

Abstract: We have previously shown that ionotropic glutamate receptors in the caudal portion of the nucleus tractus solitarii (NTS), especially in the commissural NTS, play a prominent role in the mediation of tracheobronchial cough and that substance P potentiates this reflex. This NTS region could be a site of action of some centrally acting antitussive agents and a component of a drug-sensitive gating mechanism of cough. To address these issues, we investigated changes in baseline respiratory activity and cough respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
131
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(168 citation statements)
references
References 60 publications
36
131
1
Order By: Relevance
“…It has already been shown that substance P microinjected into the caudal NTS markedly potentiates cough reflex responses (Mazzone et al, 2005;Mutolo et al, 2007) while 10 mM CP-99,994 microinjected into the same site abolishes them (Mutolo et al, 2008). Thus, we searched for a concentration of the NK 1 receptor antagonist that injected into the caudal NTS did not cause any antitussive effect under control conditions, but could abolish lisinopril-induced potentiation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has already been shown that substance P microinjected into the caudal NTS markedly potentiates cough reflex responses (Mazzone et al, 2005;Mutolo et al, 2007) while 10 mM CP-99,994 microinjected into the same site abolishes them (Mutolo et al, 2008). Thus, we searched for a concentration of the NK 1 receptor antagonist that injected into the caudal NTS did not cause any antitussive effect under control conditions, but could abolish lisinopril-induced potentiation.…”
Section: Resultsmentioning
confidence: 99%
“…All efforts were made to minimize both the number of animals used and their suffering. Experimental procedures and details about the methods employed have previously been described Mutolo et al, 2007Mutolo et al, , 2008Mutolo et al, , 2009Mutolo et al, , 2010Mutolo et al, , 2012Mutolo et al, , 2013Mutolo et al, , 2014.…”
Section: Ethical Approvalmentioning
confidence: 99%
See 3 more Smart Citations